Scheduling Process Analysis Distribution of Product Using the Distribution Requirement Planning (DRP) Method - Moh Mukhsin; M.Tajus Sobirin (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
The research aims to analyze product distribution scheduling planning, create a more efficient product distribution scheduling system by using distribution requirement planning (DRP) method in PT. Nusa Abadi Commerce is a company engaged in distribution. The results of calculations using the company method with the DRP method. In the distribution period of 2019 it showed that the DRP method of Rp. 431,510,000, - and the company's method of Rp. 563,970,000, - so the company is able to save costs by Rp. 132,460,000, or 23.49% more efficient. The results of calculations using the company method with the DRP method. The distribution period in 2020 shows that the DRP method of Rp. 368,182,500 and company method of Rp. Rp. 450,840,000, - so the company is able to save costs by Rp. 82,657,500, - or the company is able to be more efficient 18.33%. Based on the results of research that has been done in 2019 to 2020 DRP method is consistently more efficient than the company's method, therefore the company is advised to use DRP in planning distribution activities for the future period